Потоп: роман / Дмитрий Черкасов - Черкасов Дмитрий (Подводный спецназ, 2009)
Экземпляры: аб. ЦБ (2017.18.09) / Инвентарный номер: 3190 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ч-48 / ББК: 84(2Рос=Рус)6